2015
DOI: 10.1002/mdc3.12281
|View full text |Cite
|
Sign up to set email alerts
|

Substantia Nigra Echogenicity Predicts Response to Drug Withdrawal in Suspected Drug‐Induced Parkinsonism

Abstract: Introduction: Response to drug withdrawal in patients with suspected drug-induced parkinsonism (DIP) is of prognostic and therapeutic importance, but cannot be predicted solely on clinical information. The aim of this study was to validate SN hyperechogenicity (SN+) assessed by transcranial sonography as a predictor of response to drug withdrawal in this group of patients. Methods: Patients were diagnosed according to previously published criteria and prospectively included in the study. All patients were foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…However, the pTCS signs of a marked bilateral hyperechogenicity of both SN and CN did not support a DIP. Indeed, according to previous studies (24), although SN hyperechogenicity can be also observed in DIP, none of the DIP patients showed the CN hyperechogenicity. In the present case, we supposed that the improvement of rigidity and the worsening of gait might be correlated to the discontinuation of amisulpride and to the disease progression, respectively.…”
Section: Discussionmentioning
confidence: 62%
“…However, the pTCS signs of a marked bilateral hyperechogenicity of both SN and CN did not support a DIP. Indeed, according to previous studies (24), although SN hyperechogenicity can be also observed in DIP, none of the DIP patients showed the CN hyperechogenicity. In the present case, we supposed that the improvement of rigidity and the worsening of gait might be correlated to the discontinuation of amisulpride and to the disease progression, respectively.…”
Section: Discussionmentioning
confidence: 62%
“…Additionally, normal echogenicity was associated with complete recovery after drug withdrawal. 105 One prospective study found shortest onset of DIP among patients treated with typical neuroleptics (1.2 ± 0.7 months), while those treated with calcium channel blockers (CCB), flunarizine or cinnarizine, had the longest time to onset (6 ± 1.4 months). The duration of parkinsonism was also longest in the CCB group (3.2 years).…”
Section: Prognosismentioning
confidence: 99%